Handbook of Clinical Hypnosis. 1993
DOI: 10.1037/10274-015
|View full text |Cite
|
Sign up to set email alerts
|

Phobias and intense fears: Facilitating their treatment with hypnosis.

Abstract: Most clinical and experimental psychologists have been acquaintedwith clients, students, or research subjects who have described irrational and debilitating fears of specific stimuli or situations. An understanding of phobias, both their etiology and maintenance, and the role of hypnosis in their treatment should help facilitate appropriate referrals and increase the probability of successful outcomes.Several treatment approaches have been shown to be effective. This chapter concentrates on the use of hypnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1
6

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 57 publications
0
11
1
6
Order By: Relevance
“…Although we cannot exclude that more threatening tasks may lead to different results, the present findings do not support the view of higher proneness of Highs to cognitively induced threatening experiences and, thus, to possible autonomic-related diseases (Wickramasekera, 1993;Crawford and Barabasz, 1993;De Pascalis et al, 1998), as suggested by earlier observations (Sebastiani et al, 2003). In addition, previous studies on hypnotized Highs during guided imagery of unpleasant situations have indicated that, in these subjects, the autonomic responses can be efficaciously reduced by numbing suggestions even in the absence of changes in the subjective experience (Sebastiani et al, 2007).…”
Section: Discussioncontrasting
confidence: 78%
“…Although we cannot exclude that more threatening tasks may lead to different results, the present findings do not support the view of higher proneness of Highs to cognitively induced threatening experiences and, thus, to possible autonomic-related diseases (Wickramasekera, 1993;Crawford and Barabasz, 1993;De Pascalis et al, 1998), as suggested by earlier observations (Sebastiani et al, 2003). In addition, previous studies on hypnotized Highs during guided imagery of unpleasant situations have indicated that, in these subjects, the autonomic responses can be efficaciously reduced by numbing suggestions even in the absence of changes in the subjective experience (Sebastiani et al, 2007).…”
Section: Discussioncontrasting
confidence: 78%
“…In these subjects, guided imagery of the phobic object induces autonomic activation, but it is less pronounced than in low hypnotizable individuals (Lows) (Gemignani et al, 2006). Hypnosis is commonly used in desensitization procedures (Spiegel et al, 1981;Crawford and Barabasz, 1993); indeed, the cognitive characteristics of Highs (Wolpe and Lazarus, 1966;Crawford, 1989;Crawford and Barabasz, 1993;) allow them to experience suggestions quite like an in vivo exposure and to modify their autonomic responses accordingly (Sebastiani et al, 2003b;Santarcangelo and Sebastiani, 2004). Hypnosis is effective in the attenuation of both the behavioral (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…Frankel (1974) planteó hace tiempo que los pacientes fóbicos eran más sugestionables que la población normal. Estudios posteriores han puesto de manifiesto que los pacientes fóbicos puntúan consistentemente más alto en hipnotizabilidad que los controles (ver Crawford y Barabasz, 1993;González Ordi y Miguel Tobal, 2001). Según Dell (2017), estos estudios informan que entre un 46% y un 79% de los pacientes fóbicos mostrarían una alta capacidad de respuesta a la hipnosis, relación que es tanto más clara cuando hablamos de la presencia de varios miedos específicos o multifobias.…”
Section: N F O R M a C I ó N D E L A R T í C U L O Historia Del Artunclassified